Utilization of bamboo (Bamvusa blumeana) shoot powder for bangus (Chanos chanos) fish nuggets production - Santillan, Michael II (2010.)
Fish nuggets were produced from bangus (Chanos chanos) surini and rehydrated bamboo (Bambusa blumeana) shoot powder.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Bamboo shoot--Bambusa blumeana; Milkfish--Chanos chanos